Welfare Concerns for Mounted Load Carrying by Working Donkeys in Pakistan - Bukhari, Syed S. U. H.; Rosanowski, Sarah M.; McElligott, Alan G.; Parkes, Rebecca S. V. (Frontiers in Veterinary Science, 2022)
Working donkeys (Equus asinus) are vital to people’s livelihoods. They are essential for carrying goods, however globally, overloading is one of the primary welfare concerns for working donkeys. We studied mounted load carrying by donkeys and associated factors in Pakistan. A cross-sectional study of donkey owners (n = 332) was conducted, and interviews were undertaken based on a questionnaire. Owners estimated that the median weight of their donkeys was 110kg (interquartile range (IQR) 100-120kg), and that they carried a median mounted load of 81.5kg (IQR 63-99kg). We found that 87.4% of donkeys carried a load above 50% of their bodyweight ratio (BWR), the median BWR carried was 77.1% (IQR 54.5-90.7%), and 25.3% of donkeys carried above 90% BWR. Donkeys that were loaded at more than 50% BWR were more likely to adopt sternal recumbency compared to donkeys loaded with less weight (P=0.01). Donkeys carrying construction material were more likely to carry more than the median BWR, when compared to domestic loads (P<0.001). Younger donkeys aged between one and five years carried more than the median BWR compared to those aged over 15 years (P=0.03). For the models with donkeys carrying median BWR and above 90% BWR, those working in peri-urban and urban areas were more likely to carry a greater BWR than donkeys working in rural areas (P<0.001; P<0.001, respectively). For donkeys carrying more than 90% BWR, mixed breed donkeys carried higher loads compared to other breeds of donkeys (P<0.001). Overloading based on current recommendations (50% BWR) was common, with the majority (87.4%) of donkeys reported to carry more than the recommended 50% limit. This survey provides evidence of on-the-ground working practices and factors associated with mounted load carrying, which is critical for developing evidence-based recommendations for loading, in order to improve the welfare of working donkeys.